Anomalous fractionation of mercury isotopes in the Late Archean atmosphere - Aubrey L. Zerkle (Nature Portfolio, 2020)
Earth’s surface underwent a dramatic transition ~2.3 billion years ago when atmospheric oxygen first accumulated during the Great Oxidation Event. Here, the authors find that biogenic methane and volcanic emissions played a vital role in the reduced Late Archean atmosphere.